The Effect of Corporate Social Responsibility Disclosures, Board of Commissioners Composition, Public Ownership and Company Performance on Company Value - Muhammad Nuur Farid Thoha; Hanifah Fajri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The objective of this research is to investigate Disclosure of Corporate social Responsibility, Composition of The Board Of Commissioners, The Influence of Public Ownership, Company Performance to The Value of The Company (Empirical Studies On Manufactured Companies Basic Chemical and Basic Industry and Basic Chemical On Indonesian Stock Exchange In The Year 2020 To 2021. The research data and hypothesis were analyzed using linear regression analysis with the program IBM SPSS Version 26. The result of this research showed that partial Disclosure of Corporate Social Responsibility, The Influence of Public Ownership and Company Performance have no effect on the Value Of The Company. While the Return On Assets (ROA) effect to The Value Of The Company. While simultaneously showed that Disclosure of Corporate Social Responsibility, Composition of The Board Of Commissioners, The Influence of Public Ownership, Company Performance have significant effect on The Value of The Company.